A unified model of autopolyploid establishment and evolution - Oswald, Benjamin P. (2011)
The prevalence of polyploidy among flowering plants is surprising given the hurdles impeding the establishment and persistence of novel polyploid lineages. New polyploid lineages are doomed to extinction through minority cytotype exclusion except in cases of strong assortative mating, reproductive assurance through selfing or vegetative reproduction, or large intrinsic fitness advantages. Thus, much work has focused on a search for adaptive advantages associated with polyploidy, such as increased competitive ability, enhanced ecological tolerances, or increased resistance to pathogens. Yet, no consistent adaptive advantages of polyploidy have been identified. Here we develop a model of a diploid population which sporadically gives rise to novel polyploids to investigate the potential for polyploid establishment and persistence in the absence of any intrinsic fitness advantages, and with only very small levels of initial assortative mating or niche differentiation generated by dosage effects of genome duplication. Our results show that by allowing assortative mating and competitive interactions to evolve, establishment of novel polyploid lineages becomes common. Additional scenarios where adaptive optima change over time reveal that rapid environmental change promotes the fixation of polyploid lineages. These results help to explain recent empirical findings that suggest many contemporary polyploid lineages arose during the Cretaceous-Tertiary extinction without invoking adaptive advantages of polyploidy.